Endoscopic submucosal dissection using the “Clutch Cutter” for early esophageal squamous cell carcinoma - Akahoshi, Kazuya; Minoda, Yousuke; Komori, Keishi; Motomura, Yasuaki; Kubokawa, Masaru; Otsuka, Yoshihiro; Hamada, Syouhei; Fukuda, Shinichirou; Iwao, Risa; Gibo, Junya; Oya, Masafumi; Nakamura, Kazuhiko (Endoscopy, 2013)
Background and study aims: To reduce the risk of complications related to the use of knives in endoscopic submucosal dissection (ESD), we developed the Clutch Cutter which can grasp and incise targeted tissue using electrosurgical current, similarly to a biopsy technique. The study aim was to evaluate the efficacy and safety of ESD using the Clutch Cutter for early esophageal squamous cell carcinoma. Patients and methods: ESD using the Clutch Cutter was performed on 32 consecutive patients with early esophageal squamous cell carcinoma. Therapeutic efficacy and safety were assessed.Results: All lesions were treated easily and safely without unintended incision. En bloc resection was obtained in all patients. Histologically negative margins were obtained in 26/32 patients (81 %). Endoscopic perforation due to the hood in one patient (3 %), mediastinitis without endoscopic perforation in one patient (3 %), and post-ESD stricture in 5 patients (16 %) were observed. All were successfully managed conservatively. Conclusions: ESD using the Clutch Cutter appears to be a safe, easy, and technically efficient method for resecting early esophageal squamous cell carcinomas.